2013
DOI: 10.5603/ep.2013.0013
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised analysis of follicular thyroid tumours transcriptome by oligonucleotide microarray gene expression profiling

Abstract: Introduction: Mechanisms driving the invasiveness of follicular thyroid cancer (FTC) are not fully understood. In our study, we undertook an unsupervised analysis of the set of follicular thyroid tumours (adenomas (FTA) and carcinomas) to verify whether the malignant phenotype influences major sources of variability in our dataset. Material and methods:The core set of samples consisted of 52 tumours (27 FTC, 25 FTA). Total RNA was analysed by oligonucleotide microarray (HG-U133 Plus 2.0). Principal Component A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The samples and microarray data have been already used in our previous studies and are reused in the current study [18,27]. Surgical procedures on patients were conducted in Polish and German centres, at the MSC Institute—Oncology Center in Gliwice, University of Leipzig, University of Halle, and Mainz University Hospital.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples and microarray data have been already used in our previous studies and are reused in the current study [18,27]. Surgical procedures on patients were conducted in Polish and German centres, at the MSC Institute—Oncology Center in Gliwice, University of Leipzig, University of Halle, and Mainz University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…However, reproducibility of results obtained between mentioned publications was rather low. This could be a consequence of slight molecular differences between FTC and FTA [18,19] or the insufficient sample size used in these studies. Genetic alterations, such as RAS gene family somatic mutations or PAX8/PPARG translocations, although very promising in initial studies, were not found to be specific for follicular carcinoma, as these genetic alterations occurred in both FTCs and FTAs with similar frequencies [20,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with these findings, it has been shown that most cancer cells have mutations in the TCA cycle enzymes, such as succinate dehydrogenase and fumarate hydratase, leading to metabolic changes that have already been observed at the RNA level [ 84 , 85 ]. Transcriptome changes in carcinogenesis have been widely studied and a great amount of data has been published [ 86 89 ]. However, most of these data require confirmation by means of a highly accurate method of quantitative real-time PCR.…”
Section: Discussionmentioning
confidence: 99%